Social intelligence according to D. Goleman and resocialization - Anna Wojnarska (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Social intelligence (SI) is a construct distinguished for the first time by E. Thorndike in 1920; however, it was only its popularization by D. Goleman that directed attention to its possibilities to apply theoretical assumptions in practice. SI is the ability to understand the behaviors and feelings of other people and also a skill to perceive subtle signs indicating the sense and importance of a given social situation. This skill is developed very early in the relationships between the child and his/her parents/guardians and constitutes a component of an emotional-social attachment. These first experiences are of decisive importance for correct social development whereas the experiences of the adolescent age and of mature age can, to some extent, modify it. The paradox of resocialization is that the suggested influences have a lowering effect on SI. On the other hand, positive changes can be observed as a result of the creation of healing ties through small, family juvenile custody centers, interpersonal trainings, individual care after leaving the facility, strengthening the social ties of local communities, and restorative justice. The aim of the article is to draw attention to the possibility of utilizing the concept of SI in explaining the phenomenon of social maladjustment and in planning the process of resocialization (social rehabilitation).